Paleoflood History of an Oxbow Lake in the Désert River Catchment Area, Southwestern Québec, Canada - Oliva, François (Université d'Ottawa / University of Ottawa, 2013)
Most paleoflood reconstructions come from the arid dry climate of southwestern USA with very few studies being conducted in temperate climates. The study’s main objective is to determine if oxbow lakes can be used to reconstruct past flood events in temperate regions, such as the Désert River in southwestern Québec, Canada. Sediment cores were extracted and analyzed for magnetic susceptibility, loss-on-ignition and grain-size. These analyses are used to decipher evidence of flood signatures within the cores. Results show a strong relationship between past flood events and known climate variability on multi-decadal to centennial timescales. A higher frequency of floods was observed during the Little Ice Age (LIA; 1450-1850 AD) and the Dark Ages Cold Period (DACP; 300-800 AD) as compared to the Medieval Warm Period (MWP; 900-1200 AD). This study supports previous work on paleoflood hydrology using oxbow lakes as a proxy and its relationship to past hydroclimatic changes. These types of studies contribute to a better understanding of past hydroclimatic changes on regional scales that can be used to better predict future floods under a changing climate.
Keywords: Hydrology; Oxbow lake; Paleofloods